ORGANIZATIONAL LEARNING AS A DETERMINANT OF ORGANIZATIONAL AFFECTIVE COMMITMENT: EVIDENCE FROM ALGERIAN FIRMS - Imane BOUALAMAT; Mohammed BENBOUZIANE; Besma MAHMOUDI (Business Excellence and Management, 2023)
The aim of this paper is to investigate the impact of organizational learning on organizational affective commitment, two constructs that has been extensively studied in literature but rarely linked to each other, especially in the Algerian organizational research context. Using data from a hundred (100) employees and a model of discriminant functions we tried to determine the dimensions of organizational learning that has most influence on organizational affective commitment. Our results indicated that both embedded systems and empowerment are good predictors of organizational affective commitment. Managers are required to reinforce the aspects of organizational learning that predicted best employees’ affective commitment.